Dual-stressor selection alters eco-evolutionary dynamics in experimental communities - Teppo Hiltunen; Johannes Cairns; Jens Frickel; Matti Jalasvuori; Jouni Laakso; Veijo Kaitala; Sven Künzel; Emre Karakoc; Lutz Becks (PANGAEA, 2018)
Recognizing when and how rapid evolution drives ecological change is fundamental for our understanding of almost all ecological and evolutionary processes such as community assembly, genetic diversification and the stability of communities and ecosystems. Generally, rapid evolutionary change is driven through selection on genetic variation as well as affected by evolutionary constraints such as trade-offs and pleiotropic effects, all contributing to the overall rate of evolutionary change. Each of these processes can be influenced by the presence of multiple environmental stressors reducing a populations reproductive output. Potential consequences of multi-stressor selection for the occurrence and strength of the link from rapid evolution to ecological change are unclear. However, understanding these is required for predicting when rapid evolution might drive ecological change. Here we investigate how the presence of two stressors affects this link using experimental evolution with the bacterium Pseudomonas fluorescens and its predator Tetrahymena thermophila. We show that the combination of predation and sublethal antibiotic concentrations delays the evolution of anti-predator defence and antibiotic resistance compared to the presence of only one of the two stressors. Rapid defence evolution drove stabilization of the predator-prey dynamics but this link between evolution and ecology was weaker in the two-stressor environment, where defence evolution was slower, leading to less stable population dynamics. Tracking the molecular evolution of whole populations over time showed further that mutations in different genes were favoured under multi-stressor selection. Overall, we show that selection by multiple stressors can significantly alter eco-evolutionary dynamics and their predictability.
Supplement to: Hiltunen, T et al. (2018): Dual-stressor selection alters eco-evolutionary dynamics in experimental communities. Nature Ecology & Evolution, 2(12), 1974-1981, https://doi.org/10.1038/s41559-018-0701-5